Rekindling the utopian imagination: Intellectual diversity and the GLU/ICDD network - Devan Pillay; Michelle Williams (International Labour Organization (ILO), 2017)
A delegation of labour scholars and practitioners first came to our university, the University of the Witwatersrand in South Africa, in 2006, to engage with colleagues about establishing the Global Labour University on our campus. It was to be the second site after Germany, and we were all intrigued by the concept. While some of our colleagues were initially sceptical about the GLU, believing that it might be a northern imposition within the narrow confines of 20th century models that privilege formalised or established labour, corporatist social partnership and narrow workplace bargaining, we were happy to hear that some amongst the delegation had a 'Marxist' orientation and were sensitive to relations between the global North and the global South. This gave a sense of comfort to those amongst us who believed that the challenges of our time demanded a wider consideration of the totality of globalised capitalism, and its differential impacts on the world, North and South.
Keywords: 330; labour movement; collective economy; working class; Marxism; democracy facet